The operation and production in Penaeid farm: mini review - aji, ludi parwadani (Journal of Tropical Life Science, 2011)
Penaeid prawn demand in the world market has brought about a dramatic raise in the price of prawns, so, the aquaculture prawn industry also increase. Prawn farming can be divided by intensive, semi intensive or extensive culture system. Extensive culture system has low stocking densities, whereas, intensive culture (very high stocking densities) has highest level of environmental control such as recirculation system and stable ecological system. Predation and disease is the major obstacles in culture system. To deal with predation, farmers use net for covering the ponds and fencing the ponds. Disease organism such as parasites, bacteria, fungal and viruses may be eliminated through sterilization of the water. The commercial diets made from squid and white fish meal may replace fresh diet in semi-intensive culture as fish diet has a problem with preservation. Moreover, maintaining water quality such as dissolve oxygen, pH, nitrogen (ammonia and ammonium) and temperature is very important to support productivity and profitability in prawn farming. The most prominent aims at harvest are to pack the prawn in a way that avoids physical damage, minimize the quantity of prawn left on the bottom of pond, and directly chill prawn. Therefore, good management of water quality, feeding, disease, predation, and harvesting is important in prawn culture.Keywords : penaeid, prawn, culture, production, water quality